1985
DOI: 10.2307/3676631
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and Social Structure in Svalbard Rock Ptarmigan Lagopus mutus hyperboreus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Ornis Scandinavica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 5 publications
9
59
1
Order By: Relevance
“…However, our results indicated that all ptarmigan that migrated ended up close to or in an area of a sea bird colony. This is in agreement with observations written in old diaries from trappers in Svalbard (Løvenskiold 1964) and suggested by Unander and Steen (1985). Since sea bird cliffs with lush vegetation and potential winter forage for ptarmigan are widely scattered along the whole coastline of Svalbard, one should not expect any uniform migration pattern (i.e.…”
Section: Satellite Tag Performancesupporting
confidence: 79%
“…However, our results indicated that all ptarmigan that migrated ended up close to or in an area of a sea bird colony. This is in agreement with observations written in old diaries from trappers in Svalbard (Løvenskiold 1964) and suggested by Unander and Steen (1985). Since sea bird cliffs with lush vegetation and potential winter forage for ptarmigan are widely scattered along the whole coastline of Svalbard, one should not expect any uniform migration pattern (i.e.…”
Section: Satellite Tag Performancesupporting
confidence: 79%
“…In contrast with populations studied in the Scottish highlands and on subarctic and arctic grounds (Watson 1965;Unander and Steen 1985;Nielsen and Pé tursson 1995), the social organisation, space use and habitat selection in these alpine populations are poorly known (e.g. Bossert 1980Bossert , 1995Huber and Ingold 1991;De Franceschi 1992;Scherini et al 2003), and there is no information on seasonal changes in the size of home ranges of individual birds.…”
Section: Introductionmentioning
confidence: 94%
“…0.28U) and was longer in males compared to females f stride of the females . The difference in energy budget between ptarmigan sexes may be unique, however, as the extended photoperiod during the summer breeding season in Svalbard results in males defending territories for 24 h a day (Unander and Steen 1985). Significant metabolic investment has been recorded in males carrying out behaviours involved with attaining mates (Vehrencamp et al 1989;Barske et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, males often possess ornamental and colourful plumage and may be larger, compared to less conspicuous females (Dunn et al 2001;Lislevand et al 2009). Energetically costly courtship, territorial or lekking displays are exclusive to male birds giving rise to sex differences in energy budget (Unander and Steen 1985;Vehrencamp et al 1989;Barske et al 2011). Furthermore, egg formation, incubation and parental care require significant metabolic investment from only females (Parker and Holm 1990).…”
Section: Introductionmentioning
confidence: 99%